'Present realities' and the need for a 'lived experience' perspective in Brexit agri-food governance. Issue 2 (4th May 2018) - Maye, Damian; Chiswell, Hannah; Vigani, Mauro; Kirwan, James
ABSTRACT: Brexit poses a significant challenge to the future governance of the UK agri-food sector. Policy decisions that will be made in the next few years will initiate a major new phase of agrarian change and regulation. We are seeing signs of this already in agri-food policy discourse, including scenarios related to food and farming futures post-Brexit. Academic representations of Brexit and agriculture are also mostly futures-orientated. This is important analysis; however, Brexit processes are active now, rather than simply in the future, influencing the lives of farming families, farm employees, food chain actors and local communities. This paper examines how Brexit is being discussed now in two key agricultural sectors: cereals and horticulture. Regional newspaper articles are used to provide initial insights into the 'present realities' of Brexit and agriculture. By this we mean how producers, associated food chain actors and the public are engaging with Brexit now, in terms of changes they are making to their livelihoods, and expectations about future uncertainty in the present day. We conclude by making recommendations for future research to contextualize every-day, lived experiences of Brexit in agri-food governance.